Tribological origin of squeal noise in lubricated elastomer–glass contact. (23rd June 2016) - Dalzin, F.; Le Bot, A.; Perret-Liaudet, J.; Mazuyer, D.
Abstract: An experiment of squeal noise on a lubricated elastomer/glass contact is presented. The experimental device, stiff enough to be non-intrusive on the system response up to several kHz, provides the contact force, vibration velocity and contact image with a high sampling rate. It is shown that the self-excited oscillation responsible of squeal involves a single mode and that its apparition is induced by the velocity weakening of friction. Direct observation of the contact by microscopy highlights that the contact is highly heterogeneous and the number of contact spots decreases with the sliding velocity during squeal.